Review and prospects of metamaterials used to control elastic waves and vibrations - Dai, Huajie; Zhang, Xueting; Zheng, Yongju; Pei, Wanrong; Zhou, Rougang; Liu, Rong; Gong, Youping (Frontiers in Physics, 2022)
Acoustic metamaterials, artificial composite structures with exotic material properties used to control elastic waves, have become a new frontier in physics, materials science, engineering and chemistry. In this paper, the research progress and development prospect of acoustic metamaterials are reviewed. Related studies on passive acoustic metamaterials and active acoustic metamaterials are introduced and compared. Additionally, we discuss approaches to material structure design, including topology optimization approaches, as well as bio-inspired and fractal geometry-based approaches to structure design. Finally, we summarize and look forward to the prospects and directions of acoustic metamaterial research. With the development of additive manufacturing technology, the research potential of acoustic metamaterials is huge.